TOCOTRIENOL OPPOSES THE EFFECT OF LIGHT TO MODERATE ETHANOL EXPOSURES IN ELEVATED PLUS MAZE PERFORMANCE OF RATS - Dasari, Pitchaiah; Rayapati, Anandamurali; Nayak, Prasunpriya (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Tocotrienol is a naturally rare isoform of vitamin E. Consumption of ethanol is a common problem. Ethanol acts as an anxiolytic, but hastens cognitive problems. The current study is aimed to evaluate the effect of tocotrienol against ethanol-induced cognitive and anxiolytic behavior. Methods: Male albino Wistar rats were divided into two sets; one set of rats were exposed with low-to-moderate doses of ethanol for 4 weeks, while another set was exposed to tocotrienol orally (10 mg/day) plus low-to-moderate doses of ethanol for 4 weeks. Performances of rats on elevated plus maze were carried out at the end of the treatment protocol for 3 days. Video recordings were analyzed for acquisition time, retention time, and number of entries to open arms and closed arms. Numbers of protected stretch attend posture, unprotected stretch attend posture, protected head dipping, unprotected head dipping, grooming, rearing, paw licking, immobile sniffing, and fecal boli were also counted from the video recording. Results: Statistically significant influences of tocotrienol and ethanol exposures have been observed in aquisition time and retention time after 24 hrs and 48 hrs, respectively. Number of exits from the closed arms and grooming and rearing behaviors also found to be significantly influenced by tocotrienol treatment. Conclusion: From the current study, it can be concluded that tocotrienol facilitates the explorative behaviors of control rats. In addition, the current protocol of tocotrienol treatment opposes the ethanol-induced cognitive impairment as well as ethanol-induced anxiolytic activity in rats. Keywords: Tocotrienol, Ethanol, Elevated plus maze, Acquisition time, Retention time, Protected stretch attend posture, Unprotected stretch attend posture, Protected head dipping, Unprotected head dipping, Grooming, Rearing, Paw licking, Immobile sniffing.